The Role of Digital Technology in Public Response in East Nusa Tenggara - Cassandra Putri (Asian Digital Governance Problems, 2024)
Purpose: The research aims to understand how digital technology influences public engagement and decision-making processes in the region. Subjects and Methods: This qualitative study explores the role of digital technology in shaping public responses in East Nusa Tenggara (ENT), Indonesia. Data were collected through in-depth interviews with residents of ENT, focusing on their experiences and perceptions of digital technology use. Results: The findings reveal that digital technology plays a significant role in shaping public responses, enabling information dissemination, community engagement, and participatory decision-making. However, challenges such as limited access to technology and digital literacy skills hinder its full potential. This study contributes to the literature on digital technology's impact on public responses in developing regions and provides insights for policymakers and stakeholders to enhance digital technology adoption in ENT. Conclusions: This research reveals that digital technology plays a significant role in shaping public responses in East Nusa Tenggara (ENT), Indonesia. Through wider information access, more active community engagement, and more participatory decision-making, digital technology has opened up new opportunities for the people in ENT to participate in their social, political, and cultural life.